A Study of Slow-mode Shocks in the Near-Earth Magnetotail with MMS Observations and Hybrid Simulations - Nehpreet K. Walia; Kanako Seki; Takanobu Amano; Naritoshi Kitamura; Yoshifumi Saito; Tara Ahmadi; Daniel J. Gershman; Craig J. Pollock; Barbara L. Giles; Stephen A. Fuselier; Christopher T. Russell; James L. Burch (The Astrophysical Journal)
The structure of the magnetic reconnection boundary, particularly the presence of slow-mode shocks in the near-Earth magnetotail was studied by using magnetospheric multiscale (MMS) observations and 2.5D hybrid simulations. A total of 51 crossings of MMS from 2017 to 2021 were analyzed. We found that the detection percentage of slow-mode shocks in the near-Earth magnetotail is 41%–55%. Previous studies have only reported one slow-mode shock event in the near-Earth magnetotail and a slow-mode shock detection percentage of 10% or lower in the mid-to-distant magnetotail. It was observed that if the high-energy beam region data is removed from the slow-mode shock downstream observations then the detection of slow-mode shocks reduces, implying that the kinetic effects play an important role in the detection of slow-mode shocks. For the crossings where the interface was not identified as a slow-mode shock, it was found that the turbulence in those crossings can change the mass flux values and disrupt the detection of slow-mode shock. However, the macroscopic slow-mode shock-like structure stably exists around the magnetic reconnection interface, as most of the conditions for slow-mode shocks were satisfied. This result suggests that slow-mode shocks are a general feature of magnetic reconnection geometry. We find that the lack of detection of slow-mode shocks in previous observations and simulations can be explained by taking into account the kinetic structure of slow-mode shocks and the presence of turbulence.